Strategies for combating plant salinity stress: the potential of plant growth-promoting microorganisms - Acharya, Biswa R.; Gill, Satwinder Pal; Kaundal, Amita; Sandhu, Devinder (Frontiers in Plant Science, 2024)
Global climate change and the decreasing availability of high-quality water are leading to an increase in the salinization of agricultural lands. This rising salinity represents a significant abiotic stressor that detrimentally influences plant physiology and gene expression. Consequently, critical processes such as seed germination, growth, development, and yield are adversely affected. Salinity severely impacts crop yields, given that many crop plants are sensitive to salt stress. Plant growth-promoting microorganisms (PGPMs) in the rhizosphere or the rhizoplane of plants are considered the “second genome” of plants as they contribute significantly to improving the plant growth and fitness of plants in normal and when plants are under stress such as salinity. PGPMs are crucial in assisting plants to navigate the harsh conditions imposed by salt stress. By enhancing water and nutrient absorption, which is often hampered by high salinity, these microorganisms significantly improve plant resilience. They bolster the plant's defenses by increasing the production of osmoprotectants and antioxidants, mitigating salt-induced damage. Furthermore, PGPMs supply growth-promoting hormones like auxins and gibberellins and reduce levels of the stress hormone ethylene, fostering healthier plant growth. Importantly, they activate genes responsible for maintaining ion balance, a vital aspect of plant survival in saline environments. This review underscores the multifaceted roles of PGPMs in supporting plant life under salt stress, spotlighting their value for agriculture in salt-affected areas and their potential impact on global food security.